Introducción al tráfico autosimilar en redes de comunicaciones - Alzate Monroy, Marco Aurelio (Ingeniería, 2000)
Traffic is modeled as an stochastic process representing the demand that users impose on the resources of a communication network. Originally,both the demand interarrival times and the demand amounts were considered as sequences of independent variables (call durations, packet lengths,file sizes, etc.). Later on, it became apparent that the correlation among these variables were so important that new models with exponentially decaying, correlations were developed. However, recent evidence has shown that the correlation among these variables can decay much slower and persists through several time scales. This phenomenon, that impacts the network performance significatively, can be represented via fractal or self-similar models. In this paper we present the most basic concepts involved in the study of these models, hoping to help the reader to be better prepared for reading the especialized literature on the subject.